Hubungan Antara Kecerdasan Emosi Dan Keterampilan Sosial Dengan Penyesuaian Diri Pada Remaja Karang Taruna Bina Muda Dusun Ploso Desa Ngrawan Kec.Getasan Kab. Semarang - Sari, Novita; Soesilo, Tritjahjo Danny; Setyorini, Setyorini (Guidance and Counseling Study Program, Pattimura University, 2020)
As long as humans live, they need interaction with other people both individually and in groups, as social beings humans will go through stages of life that influence one another. One of them is the adolescent stage which has a big influence on his life. This study aims to determine the significance of the relationship between emotional intelligence and social skills with self- adjustment in youth youth organizations of Bina Muda Desa Ngrawan. The population in this study amounted to 30 adolescents. Data collection techniques used in this study were emotional intelligence questionnaires, social skills questionnaires, and self-adjustment questionnaires that have been developed by researchers. The data analysis technique used in this research is the Kendall-tau technique which is processed with the help of the SPSS program. 26.0 for windows. Based on the research results obtained r = 0.560 and p = 0.000 <0.05, which indicates that there is a significant relationship between emotional intelligence and social skills with self-adjustment in youth youth organizations at Ploso Hamlet, Ngrawan Village, Getasan, District Semarang. From these results it can be concluded that the higher the score for emotional intelligence and social skills, the higher the score for self-adjustment. Conversely, the lower the emotional intelligence and social skills scores, the lower the adjustment scores will be.